Bacterial communities in the natural and supplemental nests of an endangered ecosystem engineer - Megan S. Thoemmes; Michael V. Cove (Ecosphere, 2020)
Abstract Supplemental nests are often used to restore habitats for a variety of rare and endangered taxa. However, though they mimic the function of natural nests, they vary in design and construction material. We know from previous research on human buildings that these differences in architecture can alter the types of microbes to which inhabitants are exposed, and these shifts in microbial interactions can be detrimental for individual health and well‐being. Yet, no one has tested whether bacterial communities in supplemental structures are distinct from those found in natural nests. Here, we sampled the bacteria from inside supplemental nests of the endangered Key Largo woodrat (Neotoma floridana smalli). We then compared the diversity and composition of those bacteria to the bacteria collected from natural stick‐nests and the surrounding forest environment in Key Largo, Florida. In addition, we sampled woodrat bodies to assess the microbiota of nest inhabitants. We observed distinct bacterial communities in Key Largo woodrat nests, relative to the forest environment; however, we could not differentiate between the bacterial communities collected from supplemental and natural nests. Furthermore, when we considered the potential accumulation of rodent‐associated bacterial pathogens, we found no evidence of their presence in supplemental nests, in natural nests, or on the forest floor. Where we expected to see an accumulation of pathogens, we instead observed high relative abundances of bacteria from antimicrobial‐producing groups (i.e., Pseudonocardiaceae and Streptomycetaceae). The bacteria on Key Largo woodrat individuals resembled those of their nests, with a low relative abundance of potential pathogens (0.3% of sequence reads) and a high relative abundance of bacteria from antimicrobial‐producing groups. Our results suggest that, although there is some microbial interaction between nests and nest inhabitants, there are no detectable differences in the types of bacteria to which Key Largo woodrats are exposed in supplemental and natural nest structures.